2013
DOI: 10.1080/19345747.2012.725804
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Schema-Based Instruction for Improving Seventh-Grade Students’ Proportional Reasoning: A Randomized Experiment

Abstract: This study examined the effect of schema-based instruction (SBI) on seventh-grade students' mathematical problem solving performance. SBI is an instructional intervention that emphasizes the role of mathematical structure in word problems and also provides students with a heuristic to self-monitor and aid problem solving. Using a pretest-intervention-posttest-retention test design, the study compared the learning outcomes for 1,163 students in 42 classrooms who were randomly assigned to treatment (SBI) or cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 39 publications
(23 reference statements)
8
51
2
1
Order By: Relevance
“…Additional controversy arose related to the use of universal heuristics. One study criticized Pólya's (2014) universal heuristics for being too broad when in relation with middle school mathematics word problems (Jitendra et al, 2013). However, another study used Pólya's (2014) heuristic and found that students using the method produced higher posttest scores than the contrast group (Koichu et al, 2007).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additional controversy arose related to the use of universal heuristics. One study criticized Pólya's (2014) universal heuristics for being too broad when in relation with middle school mathematics word problems (Jitendra et al, 2013). However, another study used Pólya's (2014) heuristic and found that students using the method produced higher posttest scores than the contrast group (Koichu et al, 2007).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Several studies focused on acronym-related stepby-step methods such as DISC, SOLVED, and Solve it!. These studies concentrated on and the effectiveness of these methods within the mathematics classroom (Barak, 2013;Hohn & Frey, 2002;Jitendra et al, 2013;Schaefer Whitby, 2012). These studies are of particular interest because this routine procedure is essential to the implementation of SBI.…”
Section: Problem-solving Heuristics As Word Problem-solving Strategy mentioning
confidence: 99%
See 3 more Smart Citations